P3.137 Rectal Lubricant Use & Incident STI Infections at 9 US STD Clinics. (13th July 2013) - Gorbach, P M; Feaster, D J; Pines, H J; Gomez, Z; Castro, J; Bolan, R; Henn, S; Douaihy, A; Golden, M; Metsch, L
Abstract : Background: Lubricants (lube) used during receptive anal intercourse (RAI) may affect the acquisition of rectally sexually transmitted infections (rSTIs). We assessed the association between lube use during RAI and rSTI among men who have sex with men (MSM). Methods: In Project Aware, a randomised controlled trial of HIV testing and counselling at 9 US Sexually Transmitted Disease clinics, in 2010 at a 6 month visit 951 MSM completed a web survey on lube use and testing for syphilis and rectal chlamydia and gonorrhoea (rSTIs/syphilis). We used multivariable logistic regression (MVLR) to assess the association of proportion of RAI using lube and rSTIs/syphilis. Results: 589 (61.9%) of 951 men reported having receptive anal intercourse, of whom 12.9% (n = 76) were diagnosed with rSTI/syphilis. In the prior month, men reported using lube during a mean of 83% of RAI acts (median 1.0) and condoms during 54% (median 67%). The mean/median number of unprotected sex partners in the last 6 months (Upartners) was 2.64/1.0. Lube use was not directly associated with rSTI/syphilis (OR = 0.99 95% CI(.60.1.66). In MVLR adjusting for education, Upartners and condom use, the association between rSTI/syphilis and lube use increased with age and proportion of RAI with lube (interaction p = 0.02); among men age 32, the lube use during 50% and 75% of RAI acts was associated with adjusted odds ratios of 3.98 (95% CI 1.07, 14.81) and 5.03 (95% CI 1.01, 25.07), respectively and risk increased at ages greater than 32. Conclusions: Although these findings provide further evidence that frequent lubricant use during RAI can facilitate the acquisition of rectal STIs/syphilis among MSM it suggests the risk is only for older MSM. Further research is needed to assess differential risk by types of lubricants across age groups and provide rapid advice to the community who practise RAI on use of safe products.